KEANEKARAGAMAN DAN POTENSI JENIS IKAN HASIL TANGKAPAN NELAYAN DI TEMPAT PELELANGAN IKAN (TPI) PAMAYANGSARI KABUPATEN TASIKMALAYA - Nuralam, Malina Mega; Hernawati, Diana; Agustian, Dita (LP4MK STKIP PGRI Lubuklinggau, 2023)
This study aims to determine the diversity and potential of fish caught by fishermen at the Pamayangsari fish auction, Tasikmalaya Regency. This study uses descriptive quantitative methods with survey techniques. Data collection was carried out using catch data from January 2020 to October 2022 and conditional direct observations for 2 weeks in October 2022 carried out at the fish auction at Pamayangsari. The results showed that 58 fish species were identified at the fish auction of Pamayangsari, Tasikmalaya Regency, belonging to 2 classes, namely 55 species from the Actinopterygii class and 3 species from the Elasmobranchii class. As for the status of species diversity (H’) in the high category, the type wealth index (R1) is moderate, the evenness index (E) is high and stable, and the dominance index (C) is low which indicates that the community structure is quite stable. Overall catch results from January 2020 to October 2022. Based on these data the fish caught by fishermen landed at the fish auction of Pamayangsari, Tasikmalaya Regency, were quite abundant.